Kingdom of the Netherlands : Staff Report for the 1999 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This 1999 Article IV Consultation highlights that the Netherlands posted a strong economic performance during the 1990s, based on sound macroeconomic policies and complementary and interlocking reforms to fiscal policy, social security, and labor and product markets. Robust real GDP growth was combined with strong job creation and falling unemployment, as well as increasing labor participation rates. Economic activity remained strong in 1998, with real GDP expanding 3.8 percent. A slowdown that started mid-year was temporary, and growth picked up again toward the end of the year.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet